Youtube Content as an Object Of Fiduciary Guarantee in a Debt Receivable Agreement - Okta Auliazahara; Mohamad Fajri Mekka Putra (LEGAL BRIEF, 2022)
Government Regulation Number 24/2022 (PP 24/2022) has just regulated the provision of guarantees for intellectual property created by creative economy actors. YouTube content as one of the copyrighted works is included in the intellectual property in question. Even though it has been regulated, the government is still making preparations for its implementation. Where it is still not clear the scheme and its implementation. Based on this, the problems are formulated, how to measure YouTube content as a digital asset and how YouTube content can be used as an object of fiduciary security in a debt agreements. The result is that YouTube content can be regarded as a digital asset based on the economic value or income generated from the adsense feature. This income, later could become a value in fiduciary guarantees. The advice that can be given in this study is the need for good supervision in creating schemes and best implementation of making YouTube content an object of fiduciary guarantees in debt agreements.